Evidence based prevention of hamstring injuries in sport - Petersen, J.; Hölmich, P. (British Journal of Sports Medicine, 2005)
A common soft tissue injury in sports involving sprinting and jumping is the hamstring strain. A major problem with hamstring strains is the high incidence of reinjury. Muscle injuries can be classified as direct or indirect and are typically grouped into three categories according to severity. A number of potential risk factors have been proposed for hamstring strains. Only a few are evidence based and some are mainly based on theoretical assumptions. There is a lack of clinical research on the effectiveness of rehabilitation programmes for hamstring strains. Although the initial treatment of rest, ice, compression, and elevation is accepted for muscle strains, no consensus exists for their rehabilitation. Not much evidence based research has been carried out on prevention of hamstring strain. To our knowledge only two prospective studies have so far been published. As the injuries are common in football and other sports involving sprinting and jumping, there is a need for further research preferably in the form of randomised controlled trials.